Environmental journalism from Brazil: trajectory and challenges for research - Beling Loose, Eloisa (Frontiers in Communication, 2025)
This article, based on a literature review and documentary research, retraces the trajectory outlined by environmental journalism research in the Brazilian context. It does so by discussing the development of the field in other countries, especially those in the Global North, where most of the research and publications are largely concentrated. It also presents epistemological aspects of Latin American communication and the critique of environmental coloniality, present in the constitution of what can be called the ecological literacy of journalists covering the subject.